Legacies, Present, and Futures: Introduction to the Special Issue on Feminist Organizational Communication. (February 2021) - Cruz, Joëlle M.; Linabary, Jasmine R.
In this introduction to the Special Issue, we foreground our feminist journeys, discuss legacies of feminist organizational communication, and introduce the articles of the Special Issue. In the process, we imagine future possibilities of feminist work, thus charting directions for research and praxis.